BRD4 sustains p63 transcriptional program in keratinocytes - E. Foffi; A. Violante; R. Pecorari; A. M. Lena; F. Rugolo; G. Melino; E. Candi (Biology Direct)
Abstract Here, we investigated the potential interaction between bromodomain-containing protein 4 (BRD4), an established epigenetic modulator and transcriptional coactivator, and p63, a member of the p53 transcription factor family, essential for epithelial development and skin homeostasis. Our protein–protein interaction assays demonstrated a strong and conserved physical interaction between BRD4 and the p53 family members—p63, p73, and p53—suggesting a shared binding region among these proteins. While the role of BRD4 in cancer development through its interaction with p53 has been explored, the effects of BRD4 and Bromodomain and Extra Terminal (BET) inhibitors in non-transformed cells, such as keratinocytes, remain largely unknown. Our functional analyses revealed changes in cellular proliferation and differentiation in keratinocytes depleted of either p63 or BRD4, which were further supported by using the BRD4 inhibitor JQ1. Transcriptomic analyses, chromatin immunoprecipitation, and RT-qPCR indicated a synergistic mechanism between p63 and BRD4 in regulating the transcription of keratinocyte-specific p63 target genes, including HK2, FOXM1, and EVPL. This study not only highlights the complex relationship between BRD4 and p53 family members but also suggests a role for BRD4 in maintaining keratinocyte functions. Our findings pave the way for further exploration of potential therapeutic applications of BRD4 inhibitors in treating skin disorders.